Cleaner Processes for Making Laundry Soap from Vegetable Oils and an Essential Oil - Valentina-Gabi Stănescu; Vasilica Popescu; Viorica Vasilache; Gabriel Popescu; Cristina Mihaela Rîmbu; Andrei Popescu (Applied Sciences)
This article demonstrates that the quality of laundry soap obtained by hot/cold saponification of two vegetable oils (olive and coconut) and an essential oil (such as Neem, Tea Tree or Thyme) influences the effects obtained after washing textiles: cleansing capacity and antibacterial effect. The results of FTIR, SEM, EDX, thermogravimetry and colorimetry analyses are presented comparatively for hot- and cold-prepared soaps. Saponification, Iodine number and Iodine Number Saponification values are determined for each oil but also for the mixture used in soap-making. Soap quality refers to texture, hardness, foaming capacity, stability, durability, cleansing capacity after washing and antimicrobial capacity. The removal power of greasy dirt (heavy used engine oil) of these laundry soaps is higher than that of some commercial soaps, obtaining dirt visibility <2.6% after washing at 100 °C, soiling addition density SAD < 0.0229 and cleansing capacity between 80.88 and 92.16%. UV-VIS analysis confirms the presence of essential oil in soaps (even after 10 months from manufacture) but also in textiles washed with them. The essential oil imparts strong antimicrobial properties to the laundry soaps (since they do not allow for attachment or multiplication of microorganisms from the environment), which makes them particularly useful in washing and disinfecting textile products used in hospitals.